Effects of Product Quality and Promotion on Purchase Decision: A Case Study of The Lanang Suhang Soluble Coffee In Lahat Regency - Hasanah, Titi; Hestin; hardiyansyah, (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to investigate the effects of product quality and promotion on purchase decisions. This analysis is a case study involving the Lanang Suhang soluble coffee brand in Talang Agung Village, Pajar Bulan District, Lahat Regency, South Sumatera, Indonesia. Data demonstrated that the soluble coffee brand has experienced growth of as much as 10% from the last 3 years of business operation. Data were collected through questionnaires and analysed using SPSS. Results reveal that product quality has no significant effects on purchase decisions. Conversely, the promotion has significant and positive effects on purchase decisions. Simultaneously, both product quality and promotion have significant and positive impacts on purchase decision of the Lanang Suhang soluble coffee brand located in the Talang Agung Village, Pajar Bulan District, Lahat Regency, South Sumatera, Indonesia. Practical implications are discussed.